2002
DOI: 10.1111/j.1349-7006.2002.tb01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light Inhibits the Growth of B16 Melanoma Cells

Abstract: Although a number of studies have been carried out to examine the biological effects of radiation and ultraviolet radiation (UV), little is known concerning the effects of visible light. In the present study, exposure of B16 melanoma cells to blue light (wavelength 470 nm, irradiance 5.7 mW/cm 2 ) from a light-emitting diode (LED) inhibited cell growth in proportion to the period of exposure, with no increase observed in the number of dead cells. The number of B16 melanoma colonies that formed after exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 20 publications
1
42
1
1
Order By: Relevance
“…This was carried out to avoid the interaction between possible variables in the medium, such as color or soluble proteins, with the effect of blue light on the cells [7]. Our results contradict a previous paper in which the authors report that the exposure of B16 melanoma cells to blue light inhibited their growth [24]. A possible source of error for their setup is the inclusion of culture medium in the plate wells during the exposure to blue light, thereby introducing extra variables into the experiment.…”
Section: Discussioncontrasting
confidence: 84%
“…This was carried out to avoid the interaction between possible variables in the medium, such as color or soluble proteins, with the effect of blue light on the cells [7]. Our results contradict a previous paper in which the authors report that the exposure of B16 melanoma cells to blue light inhibited their growth [24]. A possible source of error for their setup is the inclusion of culture medium in the plate wells during the exposure to blue light, thereby introducing extra variables into the experiment.…”
Section: Discussioncontrasting
confidence: 84%
“…14 Animal and human studies also have demonstrated the potential utility of blue light for cancer therapy. 15,16 The mechanisms by which blue light affects cells remain unclear, but roles for cellular 14,27,28 These data support a hypothesis that blue light induced-ROS mediate, at least in part, the suppression of mitochondrial function. However, the roles of intra-and extracellular sources of the ROS in causing blue light effects, a possible role for riboflavin or flavins in vitro in generating ROS, and the degree to which these two sources interact to cause cellular responses are unclear.…”
Section: Introductionsupporting
confidence: 71%
“…15,19,23 This hypothesis predicts that riboflavin (or other extracellular components) produce ROS that migrate intracellularly and affect cell responses. The current results demonstrate that peroxide concentrations generated in…”
Section: External Peroxide Vs Intracellular Rosmentioning
confidence: 99%
“…The effect of blue light in cells has being studied by many groups [28][29][30][31][32] and it has been reported that blue light suppressed the growth (time-dependent) and also inhibited melanin synthesis in B16 melanoma [24,26]. The same effect did not occur for green and red light.…”
Section: Introductionmentioning
confidence: 91%
“…The same effect did not occur for green and red light. These authors suggested that the effect of blue light could be due to the inhibition of DNA synthesis and cell division [28,[30][31][32].…”
Section: Introductionmentioning
confidence: 97%